Oligo- Pleiodontia - Report of a rare case - A.N. Sulabha; Nikhat M. Attar; Sameer Choudhari (Al Ameen Medical College, 2019)
Numeric anomalies in the human dentition are quite common occurrence in the general population and are frequently encountered in the practice [1]. Simultaneous occurrence of tooth agenesis and supernumerary or supplemental teeth in same individual is one of rare anomalies of number in human dentition [2]. Concomitant hypohyperdontia or Oligo-pleiodontia is rare condition of unknown etiology. Concomitant hypohyperdontia (CHH) is convenient concise term introduced by Camilleri to describe the simultaneous presence of hypodontia and supernumerary teeth [3].